High ionic conduction, toughness and self-healing poly(ionic liquid)-based electrolytes enabled by synergy between flexible units and counteranions - Yang, Fu Jie; Liu, Qing Feng; Wu, Xiao Bing; He, Yu Yi; Shu, Xu Gang; Huang, Jin (RSC advances, 2021)
Polymer electrolytes offer great potential for emerging wearable electronics. However, the development of a polymer electrolyte that has high ionic conductivity, stretchability and security simultaneously is still a considerable challenge. Herein, we reported an effective approach for fabricating high-performance poly(ionic liquids) (PILs) copolymer (denoted as PIL-BA ) electrolytes by the interaction between flexible units (butyl acrylate) and counteranions. The introduction of butyl acrylate units and bis(trifluoromethane-sulfonyl)imide (TFSI − ) counteranions can significantly enhance the mobility of polymer chains, resulting in the effective improvement of ion transport, toughness and self-healability. As a result, the PIL-BA copolymer-based electrolytes containing TFSI − counterions achieved the highest ionic conductivity of 2.71 ± 0.17 mS cm −1 , 1129% of that of a PIL homopolymer electrolyte containing Cl − counterions. Moreover, the PIL-BA copolymer-based electrolytes also exhibit ultrahigh tensile strain of 1762% and good self-healable capability. Such multifunctional polymer electrolytes can potentially be applied for safe and stable wearable electronics. Polymer electrolytes offer great potential for emerging wearable electronics.